2019
DOI: 10.1055/s-0039-1693013
|View full text |Cite
|
Sign up to set email alerts
|

Homoeopathy in Cancer Pain Palliation and End of Life with Future Perspectives

Abstract: Pain is a common companion of people receiving palliative care in cancer and at the end of life. Cancer pain is multifactorial and complex. Its impact can be devastating, with increased morbidity and poor quality of life, if not treated adequately. Cancer pain management is a challenging task both due to disease process and due to treatment-related side effects; therefore, it requires a holistic approach which can be covered by homoeopathic remedies. The purpose of this article is to enlighten the scope and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…5,6,11 Other factors less well associated with infertility include semen volume and other seminal markers of epididymal, seminal vesicle function as well as genetic and environmental effects. 6,7,[11][12][13][14] Although the baseline semen quality and sperm functional parameters in fertile Indian men have been documented, the data on declining sperm count in Indian males is limited. 15 According to a study conducted in South India over a period of 13 years, it was found that the decline in sperm count was 30-31%, whereas sperm motility and morphology were reduced by 22.92% and 51.25% respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,11 Other factors less well associated with infertility include semen volume and other seminal markers of epididymal, seminal vesicle function as well as genetic and environmental effects. 6,7,[11][12][13][14] Although the baseline semen quality and sperm functional parameters in fertile Indian men have been documented, the data on declining sperm count in Indian males is limited. 15 According to a study conducted in South India over a period of 13 years, it was found that the decline in sperm count was 30-31%, whereas sperm motility and morphology were reduced by 22.92% and 51.25% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5 6 11 Other factors less well associated with infertility include semen volume and other seminal markers of epididymal, seminal vesicle function as well as genetic and environmental effects. 6 7 11 12 13 14…”
Section: Introductionmentioning
confidence: 99%
“…These gaps in relieving discomfort and the associated side effects of strong pain medications have led several researchers to investigate Homoeopathy's potential. Notably, some recent studies indicate the potential effectiveness of Homoeopathy for cancer pain management [7] . They reinforce the case for using Homoeopathic treatments which prove to be helpful in managing symptoms [4,5] .…”
Section: Introductionmentioning
confidence: 99%